Hasil Tangkapan dan Tingkat Kematangan Gonad Ikan Sembilang (Plotosus canius) - Pakidi, Chalvyn Silasa (AGRICOLA, 2023)
In this study, Sembilang fish (Plotosus canius) were studied to determine catches, gonadal maturity levels, gonadal maturity index, and fecundity in Angger Permegi Swamp. Fish sampling was carried out between September and October 2022, using gill nets with a 3 cm mesh at two research stations. The results showed that during the study period, a total catch of Sembilang fish was obtained as many as 10 fish, consisting of 6 males and 4 females. The gonad maturation stage (GMS) in Sembilang female fish was identified as GMS III and IV in September and October. Meanwhile, male Sembilang fish had GMS I, II, and III in September, and GMS III in October. The fertility of Sembilang fish ranged from 313,164 to 491,916 eggs. This was observed in fish with total lengths ranging from 30 to 44 cm and total weights ranging from 228.12 grams to 434.08 grams.